2022
DOI: 10.1101/gad.349390.122
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical imprinting sustains embryonic development and restrains placental overgrowth

Abstract: Genomic imprinting regulates parental origin-dependent monoallelic gene expression. It is mediated by either germline differential methylation of DNA (canonical imprinting) or oocyte-derived H3K27me3 (noncanonical imprinting) in mice. Depletion of Eed, an essential component of Polycomb repressive complex 2, results in genome-wide loss of H3K27me3 in oocytes, which causes loss of noncanonical imprinting (LOI) in embryos. Although Eed maternal KO (matKO) embryos show partial lethality after implantation, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Likewise, in the current study, ART produces a similar effect by inducing upregulation of the Slc38a4 amino acid transporter in mid‐gestation placentas. Notably, loss of imprinting of Slc38a4 also contributes to the placental enlargement phenotype 48,79 . Thus, canonical and non‐canonical imprinting dysregulation following ART may both contribute to placenta defects at E18.5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, in the current study, ART produces a similar effect by inducing upregulation of the Slc38a4 amino acid transporter in mid‐gestation placentas. Notably, loss of imprinting of Slc38a4 also contributes to the placental enlargement phenotype 48,79 . Thus, canonical and non‐canonical imprinting dysregulation following ART may both contribute to placenta defects at E18.5.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, we observed that FAS4 and FAS10 still exhibited better correction of most male ART DEGs in female placentas compared to male placentas (i.e., Cysltr2, Fgl2…) (Figure S4A). [45][46][47][48] (Figure 1A,B). Chromosomal location of male and female ART DEGs revealed that while DEGs were distributed across the genome, some DEGs clustered on distal chromosome 7 and 15 (Figure 2E).…”
Section: Art-associated Degs Respond To Folic Acid Supplementation In...mentioning
confidence: 99%
“…We found that uniparental expression of placenta‐specific GI genes was disrupted in SCNT‐derived placentas, demonstrating that SCNT cannot restore placenta‐specific GI 43 . Abnormal expression of placenta‐specific GI genes has been proved to be responsible for placental hypertrophy 44,45 . However, none of the human homologs of mouse placenta‐specific GI genes were imprinted in the human placenta, and the overall picture of GI in the human placenta was still unknown 33 …”
Section: Genomic Imprinting Genes In the Mouse Placentamentioning
confidence: 98%
“…43 Abnormal expression of placenta-specific GI genes has been proved to be responsible for placental hypertrophy. 44,45 However, none of the human homologs F I G U R E 1 Regulation of GI gene expression. DNA methylation of DMRs is acquired during germ cell formation and is stably maintained in the somatic cell as a genomic imprinting memory.…”
Section: G Enomi C Imprinting G Ene S In the Mous E Pl Acentamentioning
confidence: 99%
“…It should be noted that specific aberrations in epigenetic patterns can be found in preimplantation embryos, preceding SCNT-associated abnormal phenotypes such as death of embryos during the postimplantation period ( Matoba et al, 2011 ; Gao et al, 2018 ). Indeed, a recent study demonstrated that transient Xist upregulation, induced by loss of maternal polycomb PRC2, in the preimplantation period could show a detrimental ripple effect resulting in postimplantation death in mice ( Matoba et al, 2022 ). Therefore, it is important to identify other SCNT-specific changes in the epigenome or gene expression patterns during preimplantation development for further technical improvements of SCNT technology.…”
Section: Introductionmentioning
confidence: 99%